Covid-19 pandemic: subjectivities and politics in Argentina - J. I. Spólita; J. Balsa; V. Brusco (Ибероамериканские тетради)
This article analyzes the extent to which the pandemic, the confinement situation, the evaluation of the policies and attitudes of the leaders affected the subjectivities of Argentine citizens. Special attention is paid to the influence of the strong political polarization that existed previously and, also, to the ways in which the pandemic itself could have influenced political subjectivities. In addition, we have studied the reflections that, in a pandemic context, the majority of the population made about the meaning of their lives, also relating them to their political orientations. To carry out these analyses, a series of surveys were carried out throughout the year 2021 and a sample of semi-structured interviews in the months of April and May of that same year.